Local Fruits and Vegetables of Jember District That Can Increase Immunity during the Covid-19 Pandemic - Komarayanti, Sawitri; Suharso, Wiwik; Herrianto, Elfien (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The Covid-19 pandemic is closely related to immunity, a biological protection system found in the human body. This system can ward off free radicals that will enter, so it is not easy to catch the disease. If this system works properly, then a person can avoid virus attacks. Consuming fruits and vegetables is the best immune boosting way that can be done. The importance of knowing local fruits and vegetables so that it can increase immunity. Make sure fruits and vegetables are always on the diet, so that the body is always in the best condition. This research examines the diversity of local fruits and vegetables in Jember District which can increase immunity. The research method uses exploratory survey, which aims to collect information with a qualitative approach. The research instrument consists of: observation sheets, interview guidelines and documentation. The survey area covers 31 districts in Jember District. The results of the study found 28 types of local fruit that can increase immunity, namely : avocado, sweet starfruit, wuluh starfruit, cantaloupe, red dragon fruit, guava, crystal guava, lime, semboro orange, kedondong, manalagi mango, gadung mango, pineapple, papaya, banana ambon, banana berlin, banana kepok, banana nangka, banana raja, soursop, big orange, ciplukan, passion fruit, pomegranate, mangosteen and apple melon. Also found 18 types of local vegetables that can increase immunity, namely: pumpkin, tomatoes, green spinach, red spinach, leeks, oyong, large chilies, rawit chilies, katu leaves, moringa leaves, papaya leaves, kenikir, cabbage, ferns, celery, and cauliflower. Of the 28 types of local fruit found, as much as 44.8% has been cultivated. From 18 types of local vegetables, which has been cultivated by 38.9%.